2009
DOI: 10.1038/nm.2037
|View full text |Cite
|
Sign up to set email alerts
|

Nexilin mutations destabilize cardiac Z-disks and lead to dilated cardiomyopathy

Abstract: Z-disks, the mechanical integration sites of heart and skeletal muscle cells, link anchorage of myofilaments to force reception and processing. The key molecules that enable the Z-disk to persistently withstand the extreme mechanical forces during muscle contraction have not yet been identified. Here we isolated nexilin (encoded by NEXN) as a novel Z-disk protein. Loss of nexilin in zebrafish led to perturbed Z-disk stability and heart failure. To evaluate the role of nexilin in human heart failure, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
161
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(180 citation statements)
references
References 37 publications
15
161
0
1
Order By: Relevance
“…Nexilin, a newly discovered Z-disc protein, plays an important role in the pathogenesis of cardiomyopathies. Expression of nexilin proteins encoded by NEXN mutant alleles or deficiency of nexilin in zebrafish results in Z-disk damage and heart failure, indicating a dominant-negative effect of nexilin mutations (Hassel et al, 2009;Frank and Frey, 2011). In the present study, we found that H/R decreased the expression of nexilin mRNA and protein.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Nexilin, a newly discovered Z-disc protein, plays an important role in the pathogenesis of cardiomyopathies. Expression of nexilin proteins encoded by NEXN mutant alleles or deficiency of nexilin in zebrafish results in Z-disk damage and heart failure, indicating a dominant-negative effect of nexilin mutations (Hassel et al, 2009;Frank and Frey, 2011). In the present study, we found that H/R decreased the expression of nexilin mRNA and protein.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, it has been shown that nexilin is highly expressed in the heart and skeletal muscle and locates specifically to the Z-disc and that the deficiency or mutations of nexilin lead to perturbed Z-disc stability and heart failure (Hassel et al, 2009). Therefore, nexilin is considered as a novel Z-disc protein that enables the Z-discs to persistently withstand the extreme mechanical forces generated during muscle contraction (Hassel et al, 2009). Moreover, 1 deletion and 2 missense mutations in NEXN have been identified in a large cohort of patients with dilated cardiomyopathy (Hassel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate whether Myoscape deficiency interferes with key steps of zebrafish heart development, we examined the expression of cardiac chamber-specific proteins and messenger RNAs (mRNAs) by immunostainings and antisense RNA in situ hybridization, respectively, as well as the cardiac structure of Myoscape morphants by histology2930. While minimal residual Myoscape expression cannot be excluded, knockdown of Myoscape did not interfere with crucial steps of cardiogenesis, such as heart tube looping, chamber demarcation and the differentiation of ventricular and atrial cardiomyocytes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ORAI1-deficient mice die of unknown cause shortly after birth, and the role of ORAI1 in intact hearts is unknown (Gwack et al, 2008;Vig et al, 2008). To examine the role of ORAI1 in the intact heart in vivo, we used reverse genetics in zebrafish, an intriguing model organism for evaluating effects of gene loss on cardiovascular function (Hassel et al, 2009;Nasevicius and Ekker, 2000;Rottbauer et al, 2005;Sehnert et al, 2002), because the absence of blood flow for several days does not affect development of other organs (Shin and Fishman, 2002). We provide evidence that Ca 2+ entry through ORAI1 is necessary to maintain sarcomere integrity and establish proper z-disc function, in part through regulation of the localization of the calcineurin-associated protein calsarcin.…”
Section: Introductionmentioning
confidence: 99%